Towards Sustainable Farming: An Analysis And Review Of The European Union’s Agricultural Subsidy Policy - De Deyne, Laura (Journal of Sustainable Development Law and Policy, 2025)
This paper provides an overview of the most important European agricultural subsidies, which aim at promoting a more sustainable way of farming. The European Union has put these subsidies into place in order to create a better balance between agriculture and the environment. Through these ‘green’ subsidies agro-biodiversity can be protected, which is a very important goal since approximately 50% of all species in Europe depend on agricultural habitats or landscapes. The major pressures on biodiversity in agricultural land result from changes in the type and intensity of farming, which generate changes in agricultural landscapes. Such changes can result either from intensification or abandonment, both of which can be detrimental to biodiversity. Each and every single one of the discussed subsidies has its own goals and purposes. (1) Cross compliance, (2) agro-environmental measures, (3) less favoured area payments and (4) subsidies for organic farming have different objectives, which will be addressed in this paper. I will aim at analysing their overall contributions to the goal of fostering sustainable farming within the EU, through highlighting the benefits, strengths and contributions of these four types of subsidies. This paper will examine their key contents and provisions, their current level of implementation and practical measures that could be put in place to further enhance their successful implementation.